PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP MOTIVASI DAN HASIL BELAJAR SENI RUPA SISWA SMP NEGERI 30 PADANG - MELI INDAYANI, Drs. Yusron Wikarya, M.Pd., Drs. Erwin, M.Sn. (Serupa The Journal of Art Education, 2019)
The purpose of this research to know the influence of the use of cooperative learning model type tipe STAD toward motivation and outcomes studied fine arts students Junior High School 30 of Padang. The research method used was the research experiments with quantitative approach. The population of this research is all students Junior High School 30 of Padang with samples is Class VII. 4 and VII. 8 in the sampling method is purposive random sampling. This research data analysis using SPSS program v. 16.0 through t-test, with data collection methods, namely tests and questionnaires. Based on testing hypotheses 1 and 2, show the results that the existence of significant influence in the use of cooperative learning model type tipe STAD towards motivation and student learning outcome.Kata kunci: kooperatif, STAD, motivasi, hasil belajar